PENGARUH VARIABEL KEYAKINAN DIRI , BUDAYA KERJA DAN KEPEMIMPINAN TERHADAP MOTIVASI DAN KINERJA DOSEN (Studi Empiris pada Perguruan Tinggi Muhammadiyah Di Jawa Timur) - Abadi Sanosra; Ade Puspito (STIE Mandala Jember, 2014)
The purpose of this study was to determine the effect of variable confidence , work culture and leadership on motivation and performance lecturer at the Muhammadiyah University in East Java .The variables used in this study are exogenous variables , endogenous variables and intervening variables . Exogenous variables include variable self-confidence , work culture and leadership . Faculty performance is an endogenous variable, while motivation is the intermediate variables . This study used path analysis with SPSS 18 software . The population of this study were all university lecturers Muhammadiyah in East Java . The sampling method used proportional random sampling . The findings of this study states that the variable self-confidence , work culture and leadership influence on work motivation . Self-confidence , work culture and motivation affect the performance of the lecturer . Leadership does not affect the performance of the lecturer .